Study of coagulation profile and platelet indices in pregnancy induced hypertension with special reference to preeclamptic and eclamptic patients - Haldar, Biparnak; Barui, Gopinath (International Journal of Research in Medical Sciences, 2020)
Background: Hypertensive disorders of pregnancy affect about 10% of all pregnant women around the world. A variety of haematological abnormalities may occur in women with Pregnancy Induced Hypertension (PIH), thrombocytopenia being the most common. There is also a definite exaggeration of the hypercoagulable state during PIH. A strong relationship exists between the two most important causes of maternal mortality and morbidity worldwide: Preeclampsia and Post-partum hemorrhage. The aim of this study was to find out the changes that occur in the coagulation profile and platelet indices in PIH as compared to that in normal pregnancy and if they can be used as a reliable indicator of the onset and severity of Preeclampsia and eclampsia. Methods: This was a hospital based analytical prospective study carried out in R. G. Kar Medical College, between January 2017 to June 2018 on 120 patients with PIH. The study parameters included Platelet count, Platelet Distribution Width (PDW), Mean Platelet Volume (MPV), Prothrombin Time (PT) and Activated Partial Thromboplastin Time (APTT). Results: The results showed significant decrease in platelet count in preeclampsia and eclampsia patients when compared to normotensive patients. Also, there was significant increase in MPV and PDW in preeclamptic and eclamptic patients. Coagulation profile showed increased PT and APTT both in preeclamptic and eclamptic patients with eclamptic patients having significantly higher APTT than other groups. Conclusions: Thus, authors came to the conclusion that platelet indices and coagulation profile can be used as a reliable early indicator of onset and severity of preeclampsia and eclampsia.